Development and evaluation of a faraday cup electrometer for measuring and sampling atmospheric ions and charged aerosols - Panich Intra (2018)
© 2015 Taylor & Francis Group, LLC. A simple and inexpensive Faraday cup electrometer for measuring and sampling ion and aerosol charge was developed and evaluated. It consists of a Faraday housing, a filter holder, a high efficiency particulate air (HEPA) filter, Teflon® insulator, and electrometer housing. In the Faraday cup, the ion and aerosol charge entered the electrometer and then collected on the filter. All ion and aerosol charges were induced and generated an ultra-low current of less than 10 pA corresponding to the number concentration of ion and aerosol. The performance of the prototype electrometer circuit was calibrated with a current injection circuit, high-impedance current source and compared with theoretically and numerically predictions. Good agreement was found from the comparison. Experimental testing of ion and aerosol charge measurements were carried out for different operating air-flow rates for both positive and negative ions. Ion and aerosol charge measurements were also performed. Finally, this Faraday cup electrometer proved particularly useful as an ion and aerosol charge sampler and detector for both positive and negative ions.